Liquid-Assisted Grinding to Prepare a Cocrystal of Adefovir Dipivoxil Thermodynamically Less Stable than Its Neat Phase - Sungyup Jung; Insil Choi; Il Won Kim (Crystals, 2015)
Liquid-assisted grinding was employed to generate a cocrystal of adefovir dipivoxil (AD) and glutaric acid (GLU), which had not been successfully obtained through solution crystallization. The cocrystal formation was confirmed with powder X-ray diffraction, and its thermal stability and release behavior were studied through differential scanning calorimetry and dissolution experiments, respectively. The AD/GLU cocrystal was less stable than neat AD phase and the previously reported AD cocrystals with other dicarboxylic acids, such as suberic acid and succinic acid. This suggests that the intermolecular interactions of the AD/GLU cocrystal are probably weaker than the other crystal phases. The release behavior of the AD/GLU was comparable with the cocrystal with suberic acid. The current study verifies the effectiveness of the liquid-assisted grinding for the preparation of the thermodynamically less stable cocrystal phase.